2003
DOI: 10.1136/bjo.87.7.867
|View full text |Cite
|
Sign up to set email alerts
|

A 10 year retrospective survey of cataract surgery and endophthalmitis in a single eye unit: injectable lenses lower the incidence of endophthalmitis

Abstract: Aim: To study the incidence of endophthalmitis following cataract surgery over a 10 year period, and to examine ways in which this may be related to changes in surgical technique. Methods: All cases of endophthalmitis occurring over a 10 year period within a single ophthalmic unit in the United Kingdom were reviewed, and possible risk factors identified. Results: During the study period, as the technique of extracapsular cataract surgery was replaced by phacoemulsification, there was a commensurate reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 21 publications
1
59
1
6
Order By: Relevance
“…The rate of recovery depends on the clinical settings, method of specimen collection and inoculation, load of viable microbes in the inoculum, previous medical therapy, and the environment in which the inoculated plates are incubated. [17][18][19] In this study, 100% recovery rate achieved in endophthalmitis following corneal and scleral infections, whereas it accounted for 65% in post-traumatic (141 of 217), 36% in post-surgical (225 of 625), and 15.5% in EE (11 of 71). In comparison, higher recovery rates are documented in many studies from postoperative endophthalmitis (67% in EVS, 9,16 53% in South India, 20 60% in Canada, 21 67% in Australia, 22 and 75% in Sweden 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of recovery depends on the clinical settings, method of specimen collection and inoculation, load of viable microbes in the inoculum, previous medical therapy, and the environment in which the inoculated plates are incubated. [17][18][19] In this study, 100% recovery rate achieved in endophthalmitis following corneal and scleral infections, whereas it accounted for 65% in post-traumatic (141 of 217), 36% in post-surgical (225 of 625), and 15.5% in EE (11 of 71). In comparison, higher recovery rates are documented in many studies from postoperative endophthalmitis (67% in EVS, 9,16 53% in South India, 20 60% in Canada, 21 67% in Australia, 22 and 75% in Sweden 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that surgical incision size positively correlates with the probability of pathogenic bacteria entering the eye (Mayer et al, 2003). Additionally, some investigators have reported an elevated incidence of endophthalmitis by more than 300% when a scleral tunnel incision was replaced with a transparent corneal incision during cataract surgery.…”
Section: Discussionmentioning
confidence: 96%
“…28 It is postulated that this may be due to the injector preventing the lens from making contact with the ocular surface during insertion. Injectors, although available, are not routinely used in our department and were not used in any of the POE cases.…”
Section: Determining the Cause Of The Outbreakmentioning
confidence: 99%